The Conflicts of The Main Character Ken Carter in The Movie “Coach Carter” - Ida Bagus Gede Subawa Putra; I Nengah Sudipa; I Nyoman Aryawibawa (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
This study analyzes the conflicts experienced by the main character Ken Carter in the movie "Coach Carter". The study aims to identify the types of conflicts that Ken Carter experiences using Kenney's conflict theory (1986) and how he resolves them in terms of his psychological makeup and personality structure using Sigmund Freud's Psychoanalysis theory (1989). The primary data used in this study is the movie itself, and qualitative methods are used to analyze the data. The result shows that Ken Carter's conflicts are complex and varied, with external conflicts dominating the movie. The study also highlights the presence of the id, ego, and superego in Ken Carter's decision-making process, with the ego being the most dominant factor. The study's keywords are movie, main character, conflict, and psychological structure.